GAMBARAN TUMBUH KEMBANG BALITA USIA 0-24 BULAN DI POSYANDU KAMBOJA 3B - Paulus Mantur; Ngakan Putu Firman Rakha Bintang; Aninditha Kartika Patiung Adipuspito; Kartini Lidia (Universitas Nusa Cendana, 2023)
Toddlers are a golden period for the development of a child's brain, especially their physical condition dan cognition. Assessment of toddler development in this period is very important so that if an abnormality is found, it can be intervened immediately. This community service aims to see an overview of the growth dan development of toddlers aged 0-24 months at Posyandu Cambodia 3B with a cross sectional method dan a descriptive type. This community service was carried out with 44 respondents. The results showed normal nutritional status with a percentage of 81% for BB/TB, 61% for BB/U, dan 48% for TB/U. The proportion of malnutrition or malnutrition is 36%, short 45%, dan thin 18%, tall 6%, fat 2%. Based on the results, it was found that the percentage of malnutrition or undernutrition was still very high, so interventions were needed to correct the nutrition of toddlers 0-24 months. This is important to ensure the future of toddlers.